Childhood posterior circulation arterial ischemic stroke – An unusual case with a possible COVID-19-related arteriopathy - Gopal , Athulya; I, Riaz; Sugunan, Sheeja; V Hariharan, Sankar (Indian Journal of Case Reports, 2024)
Viral infections are known to increase predilection to stroke and coronavirus disease 2019 (COVID-19) has proven these concerns true. We are presenting the case of a 6-year-old previously normal male child diagnosed with posterior circulation stroke who had all etiological workups negative except for the COVID antibody. Imaging showed thrombi over the V3 segment of the vertebral artery at C1–C2 level causing near complete occlusion, with embolic infarct in the bilateral posterior inferior cerebellar artery, bilateral posterior cerebral artery, bilateral anterior inferior cerebellar artery, and the left superior cerebellar artery. The child was managed with methylprednisolone, anticoagulation, and supportive care and was able to restore near-normal neurological status within months. This case is unique in terms of the involvement of posterior circulation which is rare in the pediatric population. A possibility of inflammation-related arteriopathy secondary to infection should be considered in the etiological workup of stroke. Anti-inflammatory measures to control cytokine storm along with supportive care will ensure a good outcome.